Determination of post-mortem interval (PMI) via immunohistochemical localisation and expression of biogenic amine (cadaverine) - Lau, Frankie Pick Ping (2016)
Post- mortem interval (PMI) is the time since death until the moment the dead body of either an animal or human is discovered. The determination of PMI is of crucial importance in a forensic investigation as it would narrow down uncertainties with respect time and justifying a much more valid prima facie. Despite being extensive, most studies on PMI originated from the temperate regions. Thus, this study aimed to establish a parameter to estimate PMI via immunohistochemical localisation and expression of biogenic amine (cadaverine). Brain, liver and epaxial muscle tissue samples from three dogs were obtained at 0, 12, 18, and 24-hour post-mortem. The samples were then processed for cadaverine immunohistochemistry and H&E stained histology. Each sample was scored using an immunohistochemistry profiler software (ImageJ IHC profiler) to assess the expression of cadaverine at each interval. Results demonstrated significant differences in expression of cadaverine in a time-dependent manner for the brain (p = 0.000) and liver (p = 0.000) but none in the muscle (p = 0.817). These expression was comparable between the brain and liver but was much higher (p = 0.009 & 0.008 respectively) than that of the muscle. There was significant correlation between temperature changes against concentration of cadaverine in the brain (r = -0.898, N = 12, p = 0.000) and the liver (r = -0.958, N = 12, p = 0.000) but again none was demonstrated in the muscle. Likewise, the post-mortem changes based on H&E correlated well with those of cadaverine immunohistochemistry throughout the assessment period. Similar study should be subjected to different biogenic amines such as putrescine and spermidine. In conclusion, brain and hepatic cadaverine serves as a potential indicator for the determination of PMI.